2004
DOI: 10.2115/fiber.60.357
|View full text |Cite
|
Sign up to set email alerts
|

Structural Modification of Polyester Fibers in Supercritical Carbon Dioxide Fluid

Abstract: Several types of polyester fibers, i.e. high speed spun (HSS) fibers, partially oriented yarns (POY), and fully oriented yarns (FOY), were subjected to the supercritical CO 2 fluid treatment (SFT) at 120℃, 20MPa for 1 h and structural modifications were investigated. Large shrinkage and not a small amount of oligomer deposition on the fiber surface were observed for POY and FOY. On the contrary, as for HSS fibers produced at a spinning speed of 6 km/min the shrinkage was suppressed within 2 % as compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, the peak intensity of E ″ was a little weakened and the position was shifted to the higher temperature side. In the previous paper,5 it has been reported that such viscoelastic changes are due to binding of amorphous chains by the imperfect small crystallites generated in amorphous regions.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…However, the peak intensity of E ″ was a little weakened and the position was shifted to the higher temperature side. In the previous paper,5 it has been reported that such viscoelastic changes are due to binding of amorphous chains by the imperfect small crystallites generated in amorphous regions.…”
Section: Resultsmentioning
confidence: 95%
“…The oligomer deposition was obvious for SDY. However, the oligomer deposition was not so serious as compared with FOY5 or shin‐gosen12 produced from virgin PET pellets.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations